O ensino de piano nos Conservatórios Estaduais de Música de Minas Gerais a partir do olhar de seus professores - Maria Teresa de Souza Neves (2019)
Minas Gerais is the only state in Brazil to have 12 (twelve) State Music Conservatories (CEM), which are public and free of charge, maintained entirely by the State Secretary of Education, providing access to cultural and artistic assets to a significant portion of the population in the cities and areas where they are situated. In addition to musical education, we can assert that these institutions are also responsible for absorbing a significant number of professionals dedicated to teaching. In a survey conducted in the end of 2018, we verified that there were an expressive number of 181 piano teachers at the CEMs. Aware of the importance of these institutions, this research aimed to investigate the relationship between the formation and professional performance of piano teachers from the CEM of Minas Gerais, seeking to know aspects of their education and to understand the different meanings that these teachers attribute to their professional activity. Therefore, two different methodological approaches were chosen. The first, quantitative character, used the application of a questionnaire as a data collection instrument. The second, of qualitative character, main corpus of this research, adopted the biographical approach, conducted from semi-structured interviews, resulting in the construction of ten biographical narratives. In order to conduct the transversal analysis of the narratives, five axes were used, knowingly: data referring to the subjects' social origin and family cultural environment; the initial musical education; academic education in higher education; the professional teaching exercise and the pedagogical practices developed in the classroom; professional activities in other contexts. The CEMs proved to be a fertile field for research and analysis of vocational training offered by universities. The main results are the need to implement changes in the curricula of undergraduate courses in order to increase the formation of the instrument teacher to work in specialized schools, also including the inclusive music education and / or inclusive instrumental education. We hope that this work stimulates and enriches the discussion about higher education in music in Brazil, bring greater visibility to CEMs and point out ways for the continuing education of their teachers.